Reading women's stories: female characters in the Hebrew Bible - Petersen, John (Fortress Press, 2004)
"...delves deeply into three stories of women in the Hebrew Bible (Hannah, Deborah, and Tamar) and explores issues of reading character, plot, and point of view"--p. 4 of cover